Cultural Education for Sustaining Nusantara Religion Within Boti Indigenous Community - Wardany, Octalyna Puspa; Makin, Al; Maarif, Samsul (Pascasarjana IAIN Pontianak, 2023)
Boti indigenous community which is in Timor Tengah Selatan district, Nusa Tenggara Timur preserves and nurtures their Nusantara religion, named Uis Neno ma Uis Pah. Boti is able to live through different eras, before West influences, the colonization era, modern, and contemporary. How can the Boti indigenous community be sustained with their religion as part of custom? Is there any certain methodology which they have implemented for the regeneration so their descendants keep preserving and nurturing their Nusantara religion?. This research article is focused to answer those two questions. The research is already implemented using ethnography method, so the researcher lived in the Boti indigenous community for 13 months from October 2, 2021 until November 1, 2022. This research used decolonization as the perspective method in order to understand Boti’s Nusantara religion as well as their customs in detail and holistic including the concept and the core, so enable to do the comprehensive analyzing using proper theories of education; education and culture theories from Ki Hajar Dewantara, the Indonesia National Education Notable; Tukan and Hasfaria’s theory about Adat (Indonesia: custom); Roem Topatimasang’s theory about school; and Mori’s theory about learning method. Boti implements the cultural education as the methodology to do the regeneration so the next generation know and preserve their Nusantara religion and customs. It teaches the understanding of the transformation in life that enables them to be open and flexible for the new influences. By the implementation of division on education; modern and cultural education; Boti indigenous community is able to sustain and nurture their Nusantara religion.